Longitudinal uric acid has nonlinear association with kidney failure and mortality in chronic kidney disease - Prezelin-Reydit, Mathilde; Combe, Christian; Fouque, Denis; Frimat, Luc; Jacquelinet, Christian; Laville, Maurice; Massy, Ziad A.; Lange, Céline; Ayav, Carole; Pecoits-Filho, Roberto; Liabeuf, Sophie; Stengel, Bénédicte; et al. (Scientific reports, 2023)
We investigated the shape of the relationship between longitudinal uric acid (UA) and the hazard of kidney failure and death in chronic kidney disease (CKD) patients, and attempted to identify thresholds associated with increased hazards. We included CKD stage 3–5 patients from the CKD-REIN cohort with one serum UA measurement at cohort entry. We used cause-specific multivariate Cox models including a spline function of current values of UA (cUA), estimated from a separate linear mixed model. We followed 2781 patients (66% men, median age, 69 years) for a median of 3.2 years with a median of five longitudinal UA measures per patient. The hazard of kidney failure increased with increasing cUA, with a plateau between 6 and 10 mg/dl and a sharp increase above 11 mg/dl. The hazard of death had a U-shape relationship with cUA, with a hazard twice higher for 3 or 11 mg/dl, compared to 5 mg/dl. In CKD patients, our results indicate that UA above 10 mg/dl is a strong risk marker for kidney failure and death and that low UA levels below 5 mg/dl are associated with death before kidney failure.